Optimization of Vehicle Queue Length Using PTV Vissim at Talang Buluh Intersection, Banyuasin Regency - Melawaty Agustien; Rhaptyalyani; Muhammad Azhar Baskoro (Jurnal Teknik Sipil dan Perencanaan, 2025)
Traffic congestion is a common issue in developing metropolitan areas, impacting both economically and socially. Long vehicle queues result in delays for many vehicles, which increases travel time and contributes to deteriorating air quality due to emissions from motor vehicles at intersections. One of the influencing factors is the non-optimization of intersections due to delays. Previous studies commonly use the Highway Capacity Manual Indonesia, 2023, to analyze intersection optimization. However, this study will utilize PTV Vissim software. In planning the intersection, some factors must be considered, such as capacity, density, speed, and type. An average daily traffic survey and a road geometric survey will be conducted in the field survey. The analysis will be performed using PTV Vissim software to optimize the 3 (Three) Talang Buluh intersection in Banyuasin Regency by examining the impact of vehicle queue length and evaluating policies for improving traffic management. According to the analysis results, the data from the First Scenario shows that the maximum vehicle queue length reaches 124.02 meters, with an average delay of 18.75 seconds from the Palembang direction. In the second scenario, installing traffic signal control devices increased the queue length to 287.95 meters from the Betung direction, with the most extended delay reaching 129.52 seconds. The third scenario, which involved geometric changes at the intersection, successfully reduced the vehicle queue length to just 47.70 meters from the Palembang City direction. Additionally, the most extended delay recorded was only 11.59 seconds, demonstrating the effectiveness of this approach, though it is costly and unsuitable for short-term use. Overall, Scenario 1 can serve as a short-term solution for intersection optimization. However, if road widening improvements are feasible, Scenario 3 is the optimal solution for enhancing traffic efficiency and effectiveness, significantly reducing vehicle queues and delays. This is crucial for implementing long-term traffic management strategies at the Talang Buluh Intersection in Banyuasin Regency.